2012
DOI: 10.1177/0748233712457453
|View full text |Cite
|
Sign up to set email alerts
|

Sodium 3,5,6-trichloropyridin-2-ol poisoning

Abstract: Sodium 3,5,6-trichloropyridin-2-ol (STCP) is an important intermediate for synthesizing organophosphate insecticide chlorpyrifos. At present, chlorpyrifos is one of the world's largest species of pesticide products. Many studies have focused on the toxicity of chlorpyrifos, but few reports have looked at the toxicity mechanism of STCP. Even fewer studies have looked at STCP poisoning. With increasing production and usage of STCP, the chances of such poisoning will increase. In this study, we present a report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As early as 1993, Cheng et al surveyed 109 Chinese workers and reported that the prevalence of chloracne was 73.4% (80/109) in total and 95.2% (20/21) in a trichlorobenzene (TCB) tank area where dioxin and dibenzofurans levels were in thousands of ppm [1]. Recently, Wu et al and Niu et al reported that the workers who worked in an STCP factory in China developed chloracne and peripheral nerve damage [2,3]. For pathogenesis investigation, Liu et al found that the activation of mitogen-activated protein kinase pathway and upregulation of CK17 and TGK might play roles in the pathogenesis of chloracne related to dioxin exposures [4].…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1993, Cheng et al surveyed 109 Chinese workers and reported that the prevalence of chloracne was 73.4% (80/109) in total and 95.2% (20/21) in a trichlorobenzene (TCB) tank area where dioxin and dibenzofurans levels were in thousands of ppm [1]. Recently, Wu et al and Niu et al reported that the workers who worked in an STCP factory in China developed chloracne and peripheral nerve damage [2,3]. For pathogenesis investigation, Liu et al found that the activation of mitogen-activated protein kinase pathway and upregulation of CK17 and TGK might play roles in the pathogenesis of chloracne related to dioxin exposures [4].…”
Section: Discussionmentioning
confidence: 99%